Large Fugitive Methane Emissions From Urban Centers Along the U.S. East Coast. Issue 14 (29th July 2019) - Plant, Genevieve; Kort, Eric A.; Floerchinger, Cody; Gvakharia, Alexander; Vimont, Isaac; Sweeney, Colm
Abstract: Urban emissions remain an underexamined part of the methane budget. Here we present and interpret aircraft observations of six old and leak‐prone major cities along the East Coast of the United States. We use direct observations of methane (CH4 ), carbon dioxide (CO2 ), carbon monoxide (CO), ethane (C2 H6 ), and their correlations to quantify CH4 emissions and attribute to natural gas. We find the five largest cities emit 0.85 (0.63, 1.12) Tg CH4 /year, of which 0.75 (0.49, 1.10) Tg CH4 /year is attributed to natural gas. Our estimates, which include all thermogenic methane sources including end use, are more than twice that reported in the most recent gridded EPA inventory, which does not include end‐use emissions. These results highlight that current urban inventory estimates of natural gas emissions are substantially low, either due to underestimates of leakage, lack of inclusion of end‐use emissions, or some combination thereof. Plain Language Summary: Recent efforts to quantify fugitive methane associated with the oil and gas sector, with a particular focus on production, have resulted in significant revisions upward of emission estimates. In comparison, however, there has been limited focus on urban methane emissions. Given the volume of gas distributed and used in cities, urban losses can impact national‐level emissions. In this study we use aircraft observations of methane, carbon dioxide, carbon monoxide, and ethane to determine characteristic correlation slopes, enabling quantification of urban methane emissions and attribution to natural gas. We sample nearly 12% of the U.S. population and 4 of the 10 most populous cities, focusing on older, leak‐prone urban centers. Emission estimates are more than twice the total in the U.S. EPA inventory for these regions and are predominantly attributed to fugitive natural gas losses. Current estimates for methane emissions from the natural gas supply chain appear to require revision upward, in part possibly by including end‐use emissions, to account for these urban losses. Key Points: Aircraft observations downwind of six major cities along the U.S. East Coast are used to estimate urban methane emissions Observed urban methane estimates are about twice that reported in the Gridded EPA inventory Methane emissions from natural gas (including end use) in five cities combined exceeds nationwide emissions estimate from local distribution